Value of duplex ultrasound of carotid and lower extremity arteries in the restratification of cardiovascular risk and initiation of lipid-lowering therapy - V. V. Genkel; A. S. Kuznetsova; L. R. Pykhova; E. V. Lebedev; A. O. Salashenko; I. I. Shaposhnik (Кардиоваскулярная терапия и профилактика, 2022)
Aim. To study the role of duplex ultrasound (DU) of carotid and lower extremity arteries in the restratification of cardiovascular risk (CVR) and changing the indications for lipid-lowering therapy.Material and methods. The study included 291 patients aged 40-64 years without established atherosclerotic cardiovascular diseases. All patients underwent DU of carotid and.Results. Carotid DU make it possible to restratify 140 (65,7%) patients with low/moderate CVR (out of 213) into the category of high/very high CVR. Lower extremity artery DU resulted in the restratification of 101 (47,4%) patients with low/moderate CVR (out of 213) into the category of high/very high CVR. The use of a multifocal ultrasound technique demonstrated the highest restratification power and allowed 161 (75,6%) patients (out of 213) to be assigned to the high/very high CVR group. The use of peripheral arterial DU led to an increase in the number of high-risk patients by 2,33-3,02 times. The proportion of persons with indications for lipid-lowering therapy increased from 50 (21,0%) patients to 170 (71,4%).Conclusion. In patients aged 40-64 years without established atherosclerotic cardiovascular diseases, the use of DU of carotid and lower extremity arteries made it possible to classify 75,6% of patients with low/moderate CVR in the group of patients with high and very high CVR. According to CVR reclassification, the proportion of patients with indications for lipid-lowering therapy increased from 21,0 to 71,4% of patients.